1995
DOI: 10.1093/nar/23.15.3034
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome amplification of single cells: mathematical analysis of PEP and tagged PCR

Abstract: We construct a mathematical model for two whole genome ampliffication strtegies, prinwr extension pmampiffication (PEP) and tagged Fpoly aee chain reaction (tagged PCR). An explicit formula for the expected target yield of PEP is obtained. The distribution of the target yield and the coverage prties of these two stralegies are studied by simultions. From our studies we find that polymerase wth high processivity may increase the efficiency of PEP and tagged PCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…The usefulness of the resulting PCR products for genomic analysis was not explored; nor was its efficiency explored when starting with tiny amounts of material. An alternate approach to whole genome PCR is to use random priming with degenerate oligonucleotides (29)(30)(31)(32)(33). This method can produce large amounts of DNA starting from very minute amounts of sample, but the complexity of the DNA produced, the reproducibility of the representation, and the loss of natural restriction sites at the ends of the amplified material make the usefulness of this method somewhat limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The usefulness of the resulting PCR products for genomic analysis was not explored; nor was its efficiency explored when starting with tiny amounts of material. An alternate approach to whole genome PCR is to use random priming with degenerate oligonucleotides (29)(30)(31)(32)(33). This method can produce large amounts of DNA starting from very minute amounts of sample, but the complexity of the DNA produced, the reproducibility of the representation, and the loss of natural restriction sites at the ends of the amplified material make the usefulness of this method somewhat limited.…”
Section: Discussionmentioning
confidence: 99%
“…After transfer, the blot was hybridized in GIBCO prehybridization solution at 67°C for 2 hr. The probe was produced by random priming with the rediprime kit in the presence of 32 P␣dCTP. After 12-18 hr of hybridization, the blots were washed with standard saline phosphate͞EDTA buffer as described (6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Theoretical calculations have also predicted that tagged PCR cannot provide complete genomic coverage at low cell numbers. 24 Because MDA uses completely randomized primers, broader genomic coverage and less locus bias were achieved. 20 A performance comparison between DOP-PCR and pooled MDA for LCM cells is shown in Table 3, based on our results and that from a widely cited reference.…”
Section: Comparison To Other Wga Methodsmentioning
confidence: 99%
“…24 In practice, PEP typically generates only a moderate ϳ30-fold amplification with a ϳ100-fold locus bias. 20 A recent report demonstrated that STR analysis on an ABI sequencer was achieved using PEP products from 5000 LCM cells (Table 3).…”
Section: Comparison To Other Wga Methodsmentioning
confidence: 99%